2014
DOI: 10.1590/1982-021620146412
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento da narrativa oral e o nível de escolaridade materna

Abstract: Objetivo : verificar a narrativa oral em crianças em função do nível de escolaridade materna.Métodos : o estudo foi realizado na Escola Pública Municipal Magalhães Bastos, no bairro da Várzea no Recife, com 20 crianças da 1ª série do ensino fundamental I, com faixa etária entre sete e oito anos. Para a avaliação foi utilizado um texto e um Mp3 para a gravação das crianças narrando a história.Resultados : observou-se que a maioria das crianças encontrava-se na categoria II do esquema narrativo, grande parte apr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
2
0
3
Order By: Relevance
“…International 19 and national 20 studies have shown maternal schooling level correlates with language delays. Although this association is not always found, 21 many studies 5 , 22 , 23 , 24 have pointed to low maternal education as a risk factor for child development and academic performance, or the higher education of mothers acted as a protective factor for the development of groups of children born with some specific risk, such as low birth weight. Furthermore, a study 25 found that maternal schooling over five years was positively associated with better organization of the physical and temporal environment, more significant opportunity for variation in daily stimulation, and greater emotional and verbal involvement of the mother with the child.…”
Section: Discussionmentioning
confidence: 98%
“…International 19 and national 20 studies have shown maternal schooling level correlates with language delays. Although this association is not always found, 21 many studies 5 , 22 , 23 , 24 have pointed to low maternal education as a risk factor for child development and academic performance, or the higher education of mothers acted as a protective factor for the development of groups of children born with some specific risk, such as low birth weight. Furthermore, a study 25 found that maternal schooling over five years was positively associated with better organization of the physical and temporal environment, more significant opportunity for variation in daily stimulation, and greater emotional and verbal involvement of the mother with the child.…”
Section: Discussionmentioning
confidence: 98%
“…Os primeiros contatos comunicativos das crianças envolvem a mãe, logo o comportamento linguístico materno em suas diversas dimensões acaba moldando o percurso do desenvolvimento da linguagem (2) . Sendo assim, a forma como a linguagem é utilizada pela criança no seu processo de comunicação inicial está diretamente relacionada às relações sociais estabelecidas com outros falantes da língua (3,4) . Atualmente, o desenvolvimento da linguagem é apontado como um indicador de bem estar da criança e influi na qualidade de vida da família (5) .…”
Section: Introductionunclassified
“…Com o avançar do desenvolvimento da linguagem, as crianças passam da produção de palavras, para frases e para narrativas. O contexto de socialização familiar influencia diretamente no desenvolvimento e evolução das habilidades de narrativa oral (3) . Quando comparadas a crianças inseridas em famílias de baixo nível socioeconômico, crianças de maior nível socioeconômico apresentam melhor desempenho em habilidades narrativas (13) .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Under these circumstances, social relationships and dialogues established by the family are essential for the child's development. By facing these interactions the child inserts himself/herself in the family communicative universe, developing his/her linguistic knowledge more and more (2) .…”
Section: Introductionmentioning
confidence: 99%